If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 2)(X + 1) = (X + 1)(-1X + 3) Reorder the terms: (2 + X)(X + 1) = (X + 1)(-1X + 3) Reorder the terms: (2 + X)(1 + X) = (X + 1)(-1X + 3) Multiply (2 + X) * (1 + X) (2(1 + X) + X(1 + X)) = (X + 1)(-1X + 3) ((1 * 2 + X * 2) + X(1 + X)) = (X + 1)(-1X + 3) ((2 + 2X) + X(1 + X)) = (X + 1)(-1X + 3) (2 + 2X + (1 * X + X * X)) = (X + 1)(-1X + 3) (2 + 2X + (1X + X2)) = (X + 1)(-1X + 3) Combine like terms: 2X + 1X = 3X (2 + 3X + X2) = (X + 1)(-1X + 3) Reorder the terms: 2 + 3X + X2 = (1 + X)(-1X + 3) Reorder the terms: 2 + 3X + X2 = (1 + X)(3 + -1X) Multiply (1 + X) * (3 + -1X) 2 + 3X + X2 = (1(3 + -1X) + X(3 + -1X)) 2 + 3X + X2 = ((3 * 1 + -1X * 1) + X(3 + -1X)) 2 + 3X + X2 = ((3 + -1X) + X(3 + -1X)) 2 + 3X + X2 = (3 + -1X + (3 * X + -1X * X)) 2 + 3X + X2 = (3 + -1X + (3X + -1X2)) Combine like terms: -1X + 3X = 2X 2 + 3X + X2 = (3 + 2X + -1X2) Solving 2 + 3X + X2 = 3 + 2X + -1X2 Solving for variable 'X'. Reorder the terms: 2 + -3 + 3X + -2X + X2 + X2 = 3 + 2X + -1X2 + -3 + -2X + X2 Combine like terms: 2 + -3 = -1 -1 + 3X + -2X + X2 + X2 = 3 + 2X + -1X2 + -3 + -2X + X2 Combine like terms: 3X + -2X = 1X -1 + 1X + X2 + X2 = 3 + 2X + -1X2 + -3 + -2X + X2 Combine like terms: X2 + X2 = 2X2 -1 + 1X + 2X2 = 3 + 2X + -1X2 + -3 + -2X + X2 Reorder the terms: -1 + 1X + 2X2 = 3 + -3 + 2X + -2X + -1X2 + X2 Combine like terms: 3 + -3 = 0 -1 + 1X + 2X2 = 0 + 2X + -2X + -1X2 + X2 -1 + 1X + 2X2 = 2X + -2X + -1X2 + X2 Combine like terms: 2X + -2X = 0 -1 + 1X + 2X2 = 0 + -1X2 + X2 -1 + 1X + 2X2 = -1X2 + X2 Combine like terms: -1X2 + X2 = 0 -1 + 1X + 2X2 = 0 Factor a trinomial. (-1 + -1X)(1 + -2X) = 0Subproblem 1
Set the factor '(-1 + -1X)' equal to zero and attempt to solve: Simplifying -1 + -1X = 0 Solving -1 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1X = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1X = 0 + 1 -1X = 0 + 1 Combine like terms: 0 + 1 = 1 -1X = 1 Divide each side by '-1'. X = -1 Simplifying X = -1Subproblem 2
Set the factor '(1 + -2X)' equal to zero and attempt to solve: Simplifying 1 + -2X = 0 Solving 1 + -2X = 0 Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2X = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2X = 0 + -1 -2X = 0 + -1 Combine like terms: 0 + -1 = -1 -2X = -1 Divide each side by '-2'. X = 0.5 Simplifying X = 0.5Solution
X = {-1, 0.5}
| 4x+2=5-3x | | log(x+4)+log(x-2)=4 | | 4x-(2x+6)=20 | | 151x+47y+16z=2124 | | 50-13.28=9x | | (X+1)+6=0 | | -2x+8x-42=66 | | F(x)=-3X^3-2x+4 | | 9x-25=8x-25 | | 20=-5v-5 | | 3w+12=66 | | (k-2)x+(k+4)y+3k^2-8k+5=0 | | 3(x+6)=4x+8 | | abs(5x-4)=abs(3x+6) | | 7x-105+6x=155 | | ((5+(1*(1*(60-43))))-14)*5= | | X^4-5x^3+8x-5x+1=0 | | 24+y+3y=36 | | X^3-14x^2-32x=0 | | 6(5x+9)-6=30x+48 | | -5x-13+18=29 | | 0.67x-5=0.5x-3 | | 1.2x=21 | | n^2+n=20000 | | 12x=3/5 | | -28+10x-8x=10 | | 203+121=x^2 | | 25n+5q=65 | | 4x-6x-18=30 | | -1.33x-0.5=2(0.167x-4) | | 7m-13=15m+8 | | X^16x=0 |